Transforming Junior High School Education in the Era of the Industrial Revolution 4.0 and Society 5.0 - Zubaedi, Moh; Yanto, Heri; Formen, Ali (Universitas Negeri Semarang, 2025)
The rapid advancement of digital technologies in the era of Industrial Revolution 4.0 and Society 5.0 has significantly transformed the landscape of education. Junior high schools, as a critical stage in students' development, hold a strategic role in preparing a generation that is both technologically competent and strong in character. This study aims to analyze the challenges and strategies for integrating technology-based and character-oriented education in junior high schools to meet the demands of the digital age. Employing a library research methodology, the study reviews relevant academic literature, policy documents, and previous research findings. The results reveal a paradigm shift toward personalized and adaptive learning, the essential integration of digital literacy, and the development of 21st-century skills (4C + 1C: critical thinking, creativity, communication, collaboration, and computational thinking). Moreover, the role of teachers is transforming into facilitators and innovators. However, key challenges such as unequal infrastructure, limited ICT competencies among teachers, and disparities in access in underdeveloped regions remain prominent. The study concludes that cross-sector collaboration and adaptive educational policies are vital to building an inclusive and future-ready educational ecosystem. It recommends a holistic approach that balances technological advancement with character education to produce ethical, innovative, and resilient future citizens.